The complete chloroplast genome of Hippeastrum vittatum (Amaryllidaceae). Issue 3 (2nd July 2020) - Li, Peiling; Ren, Maofei; Zhu, Qingsong; Zhang, Yan; Xu, Hanbing; Wang, Zhiyong; Liu, Songhu; Cheng, Qin; Liang, Benguo
Abstract: Hippeastrum vittatum (L'Hér.) Herb. is a perennial herb in the Amaryllidaceae, which has been used as a medicinal and ornamental plant. Here, we assembled and characterized the complete chloroplast (cp) genome of H. vittatum by high throughput sequencing. As a result, the length of the complete cp genome is 158, 082 bp with a canonical quadripartite structure, consists of a large single-copy region (LSC) of 86, 165 bp, a small single-copy region (SSC) of 18, 283 bp, and two inverted repeat (IR) regions of 26, 817 bp, each. A total of 137 genes were identified, including 87 protein-coding genes, 42 tRNA genes, and 8 rRNA genes. The phylogenomic analysis was performed based on the complete cp genomes of 30 species, which revealed the closest relationship between H. vittatum and H. rutilum in the genus Hippeastrum.